PROSPECTS AND CHALLENGES OF IMPLEMENTING INDUSTRIAL-SCALE FERMENTED FEED IN MODERN BROILER FARMING - Zulkifli; Dedhi Yustendi; Muhammad Farhan; Rafika (Jurnal Penelitian Progresif, 2026)
The main issue raised is the gap between the theoretical potential of fermented feed, which has been proven to improve broiler performance on a small scale, and the complexity and uncertainty of its implementation on a modern industrial scale. This study aims to comprehensively analyze these strategic prospects and challenges. Using in-depth qualitative library research methods , this study synthesizes recent findings from the scientific literature. The results reveal that the prospects for industrial-scale implementation are very promising, particularly in supporting production efficiency through increasing nutrient digestibility and feed conversion, optimizing growth, reducing dependence on imports, and developing innovative products based on local ingredients. However, behind these prospects, multidimensional challenges are identified, encompassing technical-operational aspects such as the difficulty of maintaining consistent product quality and stability during mass production, distribution, and storage, as well as economic challenges such as high initial investment and the need for changes in feed management at the farm level. The study concludes that the successful adoption of this technology depends on the ability to integrate biotechnology innovation with robust supply chain management, appropriate business strategies, and ongoing educational programs. As an implementation, strategic collaboration is needed between the feed industry, government, and the research world to conduct pilot projects, develop operational standards, and formulate supporting policies that can mitigate risks and accelerate the realization of the potential of fermented feed towards a more efficient, independent, and sustainable broiler farming system.